Neuromodulation to Treat Substance Use Disorders in People With Schizophrenia and Other Psychoses: A Systematic Review - Johnstone, Samantha; Sorkhou, Maryam; Al-Saghir, Nada; Lowe, Darby J. E.; Steele, Vaughn R.; Pearlson, Godfrey D.; Castle, David J.; George, Tony P. (Frontiers in Psychiatry, 2022)
Background: Substance use disorders (SUDs) are a common yet poorly studied comorbidity in individuals with schizophrenia. The co-occurrence of the two complicates recovery and interferes with pharmacological and behavioural treatment response and adherence. Recently, researchers have been exploring both invasive and non-invasive neuromodulation techniques as potential treatment methods for SUDs. We review the evidence that neuromodulation techniques may reduce substance craving and consumption in individuals with schizophrenia. Methods: A comprehensive literature search of PubMed, MEDLINE and PsycINFO databases was conducted (N=1,432). Of these, we identified seven studies examining the effects of repetitive transcranial magnetic stimulation (rTMS) and two studies using transcranial direct current stimulation (tDCS) on drug consumption and craving in schizophrenia. Results: Despite the limited number of studies in this area, the evidence suggests that rTMS to the dorsolateral prefrontal cortex (DLPFC) may reduce cannabis and tobacco use in patients with schizophrenia and SCA. Findings with tDCS, however, were inconclusive. Discussion: Our systematic review suggests that rTMS applied to DLPFC is a safe and promising therapeutic technique for the management of comorbid schizophrenia and SUDs, with the majority of the evidence in tobacco use disorder. However, there was substantial heterogeneity in study methods, underscoring the need to optimize stimulation parameters (e.g., frequency, duration, and target regions). Larger clinical trials are needed to establish the efficacy of rTMS in reducing drug consumption and craving in psychotic patients, ideally in comparison to existing pharmacological and behavioural interventions.